Analysis of Energy Accumulation and Dispersion Evolution of a Thick Hard Roof and Dynamic Load Response of the Hydraulic Support in a Large Space Stope - Bu, Qingwei; Tu, Min; Zhang, Xiangyang; Zhang, Ming; Zhao, Qingchong (Frontiers in Earth Science, 2022)
Aiming at the mining disaster of a thick hard roof, based on the analysis of the mining instability influence of the thick hard roof, this study constructs the mining bearing mechanical model of the thick hard roof by using mechanical theory and obtains the mechanical distribution equation of mining bearing and energy accumulation, the mining instability energy release equation, and the dynamic load response equation of a hydraulic support in the working face, as well as the dynamic load response characteristics of the hydraulic support in the working face, putting forward the technical countermeasures for the strong dynamic pressure control of the thick hard roof in the working face. This research shows that 1) the larger the overburden load and suspension span of the thick hard roof, the more serious the mining bearing state and energy accumulation evolution; the greater the rock thickness and elastic modulus of the thick hard roof, the greater the flexural stiffness of the roof, resulting in the increase of the roof mining limit breaking span, which indirectly aggravates the mining bearing state and self-energy accumulation evolution; 2) the dynamic support resistance of the hydraulic support is composed of the dynamic support resistance caused by the release of elastic energy accumulated by mining of the thick hard roof, the work done by the overlying load, and the static support resistance caused by the direct roof gravity; 3) the dynamic support resistance caused by the work of the overlying load accounts for the highest proportion, followed by the dynamic support resistance caused by the release of mining elastic energy by the thick hard roof; the cause of mining instability and the strong dynamic pressure of the thick hard roof lie in the large span of the mining suspended roof, and the large-scale mining suspension structure of the thick hard roof leads to a high overlying load and large accumulated energy; and 4) the mining instability of the thick hard roof leads to a strong dynamic load response of the hydraulic support; adopting pre-splitting and roof cutting technology to reduce the breaking span of the thick hard roof and reducing the impact dynamic load caused by mining instability of the thick hard roof can effectively eliminate the potential safety hazard of overlimit bearing of the hydraulic support.